Factors of Management Affecting the Innovative Behavior of Educational Personnel in the Central Educational Innovation Area: Factors of Management Affecting the Innovative Behavior of Educational Personnel in the Central Educational Innovation Area - Moonlasart, Tippawan; Kumhom, Naitawan; Youtakew , Natthaphumin (RATANABUTH JOURNAL, 2026)
Educational Innovation Area of Central Thailand, who were selected based on the sample size determination table developed by Cochran. The research instrument was a questionnaire. The statistical methods used for data analysis were mean, standard deviation, Pearson’s product-moment correlation coefficient, and stepwise multiple regression analysis. The results revealed that administrative factors had a statistically significant positive relationship with the innovative behavior of educational personnel in the Educational Innovation Area of Central Thailand at the .01 level. The overall relationship was at a high level (r = .831). Among the factors, self-efficacy in being an educational innovator had the strongest relationship, followed by acceptance of educational innovation, social support, modeling, achievement motivation, and future orientation and self-control, respectively. The results of the stepwise multiple regression analysis indicated that self-efficacy in being an educational innovator, acceptance of educational innovation, social support, and achievement motivation significantly predicted innovative behavior among educational personnel at the .01 level. These four factors jointly explained 73.50% of the variance in innovative behavior (R = .857, R² = .735, Adjusted R² = .731). Self-efficacy in being an educational innovator had the highest predictive power (β = .401), followed by acceptance of educational innovation (β = .314), social support (β = .219), and achievement motivation (β = .165), respectively.